2017
DOI: 10.7860/jcdr/2017/25837.10238
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study on Knowledge and Attitude towards Risk Factors, Early Identification and Intervention of Infant Hearing Loss among Puerperal Mothers- A Short Survey

Abstract: Aim: The present study was done to determine the mothers' knowledge and their attitude towards risk factors of infant hearing loss, its early identification and intervention and also awareness of effect of consanguinity on hearing loss. Materials and Methods:In this cross-sectional questionnaire survey study, a total of 100 mothers were interviewed using the questionnaire which consisted of three sections namely risk factors, early identification and early intervention of hearing loss. Chi-square test was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Sedehi et al [12] reported that 38.8% of the unmarried youth had agreed to consanguineous marriage whereas in our study 23% of the unmarried participants and 33.7% of the total participants supported consanguineous marriage either for themselves or family members, which is an alarming number considering the wide range of possible genetic diseases it can cause. Our study shows that the majority of the participants were aware about risk factors like ear infections (72%) and ear/head injury (72.7%) which are similar to the results reported by Dudda et al [13] and Swanepoel et al [14]. Dudda et al [13] showed moderate to high levels of awareness on established causes like family history (72%), consanguinity (56%) and benefits of early identification (66%) whereas in our study, more than half of the participants had no knowledge regarding these factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Sedehi et al [12] reported that 38.8% of the unmarried youth had agreed to consanguineous marriage whereas in our study 23% of the unmarried participants and 33.7% of the total participants supported consanguineous marriage either for themselves or family members, which is an alarming number considering the wide range of possible genetic diseases it can cause. Our study shows that the majority of the participants were aware about risk factors like ear infections (72%) and ear/head injury (72.7%) which are similar to the results reported by Dudda et al [13] and Swanepoel et al [14]. Dudda et al [13] showed moderate to high levels of awareness on established causes like family history (72%), consanguinity (56%) and benefits of early identification (66%) whereas in our study, more than half of the participants had no knowledge regarding these factors.…”
Section: Discussionsupporting
confidence: 90%
“…Our study shows that the majority of the participants were aware about risk factors like ear infections (72%) and ear/head injury (72.7%) which are similar to the results reported by Dudda et al [13] and Swanepoel et al [14]. Dudda et al [13] showed moderate to high levels of awareness on established causes like family history (72%), consanguinity (56%) and benefits of early identification (66%) whereas in our study, more than half of the participants had no knowledge regarding these factors. The same study reported that the mothers were least aware of other risk factors and management of hearing loss, which is similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, parents play a critical role in early intervention and proper and timely educational placement of a child. 9 By assessing their knowledge and awareness through this developed questionnaire, various steps can be taken to impart adequate knowledge to the parents on diverse issues and aspects related to risk identification at an early stage for early rehabilitation and out coming the attitudinal barrier on mainstreaming among the public. Hence, depending upon the cut-off scores obtained, more awareness related orientation can be provided by counselling through pamphlet, videos, pictures, and testimonies to impart knowledge related to risk factors and the need for early rehabilitation, which will in turn help for better placement and mainstreaming of the child in school.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that parents are aware of some of the causes like head injury, slap to the ear and family history of hearing loss, and less awareness concerning the early identification and intervention. 9 The knowledge of mothers in Durban, South Africa, regarding risk factors of hearing loss in infants and their responsiveness to audiology services was studied. The result reports that there was average awareness about the risk factors but less awareness about the audiological services.…”
mentioning
confidence: 99%
“…Olusanya, Luxon and Wirz (2006) showed similar results, with good maternal knowledge of the risks related to measles, otitis media, birth asphyxia, and jaundice. It is crucial to educate mothers on various risk factors and management of hearing loss so as to reduce its consequences (Dudda et al,2017). In South Africa, implementing risk-based hearing screening programmes, which involves screening of newborns with known risk factors for hearing loss, is a more reasonable interim approach to follow in order to ensure early identification of children with hearing loss on the various levels of service delivery contexts within the South African healthcare system (Kanji, 2016).…”
Section: Discussionmentioning
confidence: 99%